Cellulose nanocrystals Pickering emulsion incorporated chitosan coatings for improving storability of postharvest Bartlett pears (Pyrus communis) during long-term cold storage. (November 2018) - Deng, Zilong; Jung, Jooyeoun; Simonsen, John; Zhao, Yanyun
Abstract: Cellulose nanocrystal (CNC) Pickering emulsion was prepared and incorporated into chitosan (CH) coatings (CH-PCNC, 0.1% CNC/3% oleic acid/2% CH) for improving hydrophobicity of coatings on Bartlett pears during long-term cold storage (1.7 °C and 90% RH). FTIR analysis of CH-PCNC films stored at both 43% and 83% RH showed no large absorption band at ∼3300–3400 cm −1 (–OH stretching), whereas that of CNC reinforced CH film (CH-CNC) stored at 83% RH exhibited a large increase compared to film stored at 43% RH. Water vapor permeability (0.06 g mm/m 2 ·d·Pa) of CH-PCNC film was significantly ( P < 0.05) lower than that of CH-CNC film (0.251 g mm/m 2 ·d·Pa). These results suggested that CH-PCNC matrix is more stable than CH-CNC at high RH. CH-PCNC coatings significantly ( P < 0.05) delayed ripening and reduced senescent scalding of Bartlett pears compared to Semperfresh™ coating during 3 months of storage. This study demonstrated the possibility of using CNC Pickering emulsions for enhancing the stability of hydrophilic chitosan-based coatings. Graphical abstract: Image 1 Highlights: Cellulose nanocrystal Pickering emulsion was incorporated into chitosan coating (CH-PCNC). CH-PCNC was more stable than CNC reinforced CH coating at high humidity. Pears were coated by CH-PCNC, showing well adhesion on fruit surface. CH-PCNC delayed ripening and improved storability of pears during cold storage.